Clonal variation in chemical wood characteristics in Hanönü (Kastamonu) Günlüburun black pine (Pinus nigraArnold. subsp.Pallasiana(Lamb.) Holmboe) seed orchard - Yigit, Nurcan; Sevik, Hakan; Cetin, Mehmet; Gul, Levent (Informa UK Limited, 2016)
ABSTRACTScientific evidence suggests forest cover across the world is gradually decreasing while the world’s population is rapidly increasing. In line with this, the demand on raw wood is also increasing, making it impossible for the already limited natural resources to meet human needs in proportion to the increasing population size. To counter this, there is a need to increase the variety and availability of timber through genetic improvement. This has been seen in genetic improvement studies in forestry which have resulted in seed orchard establishments; however, the genetic variation in these seed orchards continues to be a topic of debate. This study aims to determine the clonal variation in chemical characteristics in a Hanonu (Kastamonu) Gunluburun black pine (Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe) seed orchard. The analysis shows differences between the clones were seen at the 99.9% confidence level. Ash content, NaOH, extractive substance, and hot water solubility exhibited the hi...
Keywords: 15. Life on land